The impact of international care networks on the clinical management of constitutional mismatch repair deficiency (CMMRD): a review of recent developments - Hans F. A. Vasen; Katharina Wimmer; Mariëtte van Kouwen; Léa Guerrini-Rousseau; Daniela Gattini; Lucie Stengs; Uri Tabori; Chrystelle Colas; Anirban Das (Familial Cancer, 2026)
Constitutional mismatch repair deficiency (CMMRD) is a rare and likely the most penetrant cancer predisposition syndrome caused by biallelic germline variants in a mismatch repair gene. Patients typically develop a spectrum of malignancies, including brain tumors, gastrointestinal cancers, and hematological neoplasms within the first two decades of life. Since its initial description in 1999, two international consortia, the International Replication Repair Deficiency Consortium (IRRDC) and Care for CMMRD (C4CMMRD), have been established to better understand the syndrome, leading to the creation of diagnostic guidelines and surveillance protocols. This review summarizes recent data on the CMMRD tumor spectrum and discusses the consortia’s updated diagnostic criteria and management guidelines, including novel blood-based assays for detecting constitutional microsatellite instability. Furthermore, we present the initial results and subsequent adjustments to international surveillance protocols. Finally, we discuss the demonstrated efficacy of immune checkpoint inhibitor (ICI) treatment, a key therapeutic advancement for CMMRD patients.

Shake-table testing of a stone masonry building aggregate: overview of blind prediction study - I. Tomić; A. Penna; M. DeJong; C. Butenweg; A. A. Correia; P. X. Candeias; I. Senaldi; G. Guerrini; D. Malomo; B. Wilding; D. Pettinga; M. Spanenburg; et al. (Bulletin of Earthquake Engineering, 2024)
City centres of Europe are often composed of unreinforced masonry structural aggregates, whose seismic response is challenging to predict. To advance the state of the art on the seismic response of these aggregates, the Adjacent Interacting Masonry Structures (AIMS) subproject from Horizon 2020 project Seismology and Earthquake Engineering Research Infrastructure Alliance for Europe (SERA) provides shake-table test data of a two-unit, double-leaf stone masonry aggregate subjected to two horizontal components of dynamic excitation. A blind prediction was organized with participants from academia and industry to test modelling approaches and assumptions and to learn about the extent of uncertainty in modelling for such masonry aggregates. The participants were provided with the full set of material and geometrical data, construction details and original seismic input and asked to predict prior to the test the expected seismic response in terms of damage mechanisms, base-shear forces, and roof displacements. The modelling approaches used differ significantly in the level of detail and the modelling assumptions. This paper provides an overview of the adopted modelling approaches and their subsequent predictions. It further discusses the range of assumptions made when modelling masonry walls, floors and connections, and aims at discovering how the common solutions regarding modelling masonry in general, and masonry aggregates in particular, affect the results. The results are evaluated both in terms of damage mechanisms, base shear forces, displacements and interface openings in both directions, and then compared with the experimental results. The modelling approaches featuring Discrete Element Method (DEM) led to the best predictions in terms of displacements, while a submission using rigid block limit analysis led to the best prediction in terms of damage mechanisms. Large coefficients of variation of predicted displacements and general underestimation of displacements in comparison with experimental results, except for DEM models, highlight the need for further consensus building on suitable modelling assumptions for such masonry aggregates.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Seismic performance of bridges during the 2016 Central Italy earthquakes - L. Di Sarno; F. da Porto; G. Guerrini; P. M. Calvi; G. Camata; A. Prota (Bulletin of Earthquake Engineering, 2019)

Cost Savings in Wastewater Treatment Processes: the Role of Environmental and Operational Drivers - A. Guerrini; G. Romano; L. Carosi; F. Mancuso (Water Resources Management, 2017)

Identity by descent fine mapping of familial adult myoclonus epilepsy (FAME) to 2p11.2–2q11.2 - Lyndal Henden; Saskia Freytag; Zaid Afawi; Sara Baldassari; Samuel F. Berkovic; Francesca Bisulli; Laura Canafoglia; Giorgio Casari; Douglas Ewan Crompton; Christel Depienne; Jozef Gecz; Renzo Guerrini; et al. (Human Genetics, 2016)

Species-specific probe, based on 18S rDNA sequence, could be used for identification of the mucilage producer microalga Gonyaulax fragilis (Dinophyta) - M. Riccardi; F. Guerrini; F. Tinti; L. Boni; R. Pistocchi (Hydrobiologia, 2007)

Species-specific probe, based on 18S rDNA sequence, could be used for identification of the mucilage producer microalga Gonyaulax fragilis (Dinophyta) - F. Tinti; L. Boni; R. Pistocchi; M. Riccardi; F. Guerrini (Hydrobiologia, 2007)

Increased production of extra- and intracellular metal-ligands in phytoplankton exposed to copper and cadmium - R. Pistocchi; M.A. Mormile; F. Guerrini; G. Isani; L. Boni (Journal of Applied Phycology, 2000)